Determinan Pembiayaan Bermasalah Produk Akad Murabahah pada Bank Umum Syariah di Indonesia - Dedi Mardianto (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
This research was conducted to analyze the factors that influence the problematic financing of murabaha contract products at Islamic commercial banks in 2017-2021 with research samples of Islamic commercial banks in Islamic banking statistics published by the Financial Services Authority (OJK) and analyzed using multiple linear regression. The results of the analysis obtained a significant negative effect of murabahah financing and interest rates on problematic financing of murabahah contract products. Meanwhile, capital adequacy has a negative but not significant effect on financing problematic murabahah contract products at Islamic commercial banks in Indonesia from 2017 to 2021. So that additional capital is carried out by banks, it does not allow for a decrease in problematic financing of murabahah contract products at Islamic commercial banks.